O suicídio de colegas de profissão: a percepção dos médicos - Simas, Tassiéli Mendes (2017)
This research aimed to investigate physicians’ perceptions concerning their profession colleagues’ suicides. Therefore, we carried out a qualitative exploratory study. Nine physicians between 34 and 57 years old, working in a public hospital in Rio Grande do Sul, participated in the study. The number of participants was delimited by the saturation criterion. The instrument used for data collection was a semi-directed interview. The interviews were recorded, transcribed integrally and analyzed from content analysis. The ethical principles were respected in order to protect the rights of the participants, with the formalization of participation through the Free and Informed Consent Form. Among the results, we noticed that the participants considered to be related to the suicide of their colleagues: depression; burnout syndrome due to emotional exhaustion; the indiscriminate use of alcohol and drugs; their self-medication, because physitians often refuse to seek professional help. In addition, we are concerned about the training of medical students, quite demanding in technics, what is related to suicides. We concluded that there is a need for a space aimed at a mental health care of physicians and also medical students, so that cases of suicide are well treated and prevented, such as a review of medical training parameters.